Pengaruh Tingkat Inflasi, Fluktuasi Harga Emas, Dan Jumlah Nasabah Terhadap Penyaluran Pembiayaan Rahn Pada PT. Pegadaian (PERSERO) Periode 2012-2021 - Diah Puspita Sari; Budiman, Septian (DPPM Universitas Pelita Bangsa, 2023)
This study aims to analyze PT Pegadaian (PERSERO)'s distribution of rahn financing, which is influenced by inflation rates, fluctuations in gold prices, and the number of customers. This research is quantitative, using secondary data. In collecting data, this study uses two methods, namely the method of documentation and the method of literature. The samples used were 10 samples from PT. Pegadaian's financial statements from 2012 to 2021. In this study, the data analysis technique used is multiple linear regression analysis. Data processing in this study uses e-views software version 10. Partial test results state that (1) the inflation rate has a negative and insignificant effect on the distribution of Rahn financing; (2) fluctuations in the price of gold have a significant effect on the distribution of Rahn financing; and (3) the number of customers has a negative and insignificant effect on the distribution of Rahn financing. Rahn's financing distribution is influenced by the inflation rate, gold price fluctuations, and the number of customers based on simultaneous test results.